2018
DOI: 10.1123/ijspp.2017-0506
|View full text |Cite
|
Sign up to set email alerts
|

Positional Comparisons in the Impact of Fatigue on Movement Patterns in Hockey

Abstract: During competitive match play, a degree of positional variation can be observed across QTRs. The relative distance and the number of accelerations and decelerations at moderate and high intensity decreased across QTRs. No between-QTRs differences in high-speed activity were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…The characteristics of the 19 included studies are summarised in Table 3. One study investigated American Football [42], two Australian Football [43, 44], one hockey [18], four rugby league [29, 4547], three rugby sevens [36, 48, 49], two rugby union [41, 50] and six soccer [10, 16, 17, 19, 20, 51]. Across all seven team sports investigated, the total sample included 469 players with a mean age ranging from 18 to 29 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the 19 included studies are summarised in Table 3. One study investigated American Football [42], two Australian Football [43, 44], one hockey [18], four rugby league [29, 4547], three rugby sevens [36, 48, 49], two rugby union [41, 50] and six soccer [10, 16, 17, 19, 20, 51]. Across all seven team sports investigated, the total sample included 469 players with a mean age ranging from 18 to 29 years.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest amount of uncertainty (65%) was in the data processing domain, as only eight studies [17, 19, 20, 36, 43, 4648] reported the MED. The lowest risk of bias (35% low RoB) was the normative profile domain, in which nearly half (45%, n = 9) of the studies [16, 18, 41–44, 46, 48, 50, 51] used greater than ten matches in total, and over half (60%, n = 12) of the studies [18, 20, 29, 4247, 50, 51] reported position-specific acceleration and deceleration data. The number of matches used to characterise the average high-intensity acceleration and deceleration demands ranged between 1 and 42.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations